Costs of planning and implementing the CDC's Colorectal Cancer Screening Demonstration Program. (18th July 2013) - Subramanian, Sujha; Tangka, Florence K. L.; Hoover, Sonja; Beebe, Maggie C.; DeGroff, Amy; Royalty, Janet; Seeff, Laura C.
Abstract : BACKGROUND: The Centers for Disease Control and Prevention (CDC) initiated the Colorectal Cancer Screening Demonstration Program (CRCSDP) to explore the feasibility of establishing a large‐scale colorectal cancer screening program for underserved populations in the United States. The authors of the current report provide a detailed description of the total program costs (clinical and nonclinical) incurred during both the start‐up and service delivery (screening) phases of the 4‐year program. METHODS: Tailored cost questionnaires were completed by staff at the 5 CRCSDP sites. Cost data were collected for clinical services and nonclinical programmatic activities (program management, data collection, and tracking, etc). In‐kind contributions also were measured and were assigned monetary values. RESULTS: Nearly 11.3 million was expended by the 5 sites over 4 years, and 71% was provided by the CDC. The proportion of funding spent on clinical service delivery and service delivery/patient support comprised the largest proportion of cost during the implementation phase (years 2‐4). The per‐person nonclinical cost comprised a substantial portion of total costs for all sites. The cost per person screened varied across the 5 sites and by screening method. Overall, economies of scale were observed, with lower costs resulting from larger numbers of individuals screened. CONCLUSIONS: Programs incur substantial variable costs related to clinical services and semivariable costs related to nonclinical services. Therefore, programs that serve large populations are likely to achieve a lower cost per person. Cancer 2013;119(15 suppl):2855–62. © 2013 American Cancer Society . Abstract : This report provides a detailed description of the total program (clinical and nonclinical) costs incurred during both the start‐up and service delivery (screening) phases of the 4‐year Colorectal Cancer Screening Demonstration Program implemented by the Centers for Disease Control and Prevention.